Effect of some fruit extracts on tenderness and some chemical and physical characteristics of cow meat - Shirwan Mohammed M Amin; Ayad Bakir Mahmud (University of Thi-Qar Journal of agricultural research, 2025)
This study investigated the effects of pineapple (Ananas comosus) and kiwifruit (Actinidia deliciosa) extracts on the chemical composition, physical characteristics, and sensory qualities of cow longissimus dorsi muscle during frozen storage (0, 30, 60, and 90 days). We examined five distinct treatments: T1 (control), T2 (100% pineapple), T3 (50% pineapple), T4 (100% kiwifruit), and T5 (50% kiwifruit). Proximate analysis revealed significant treatment effects (p < 0.05). The moisture content was maximal in T2 (74.29%) and minimal in T4 (71.60%). The protein content in T2 (16.76%) was inferior to that of the other treatments (about 18%). No changes in treatment for fat content were observed; however, it increased with storage length. The ash percentage reached highest perecentage in T4 at 0.93% and was lowest in T1 at 0.62%. The physical quality traits varied significantly: T4 and T5 exhibited the highest water-holding capacity (WHC) at 45.63%, whilst T2 had the lowest at 42.65%. The cooking loss was most in T2 (48.23%) and minimal in T1 (39.30%). Water holding capacity (WHC) peaked between 30 and 60 days, whereas cooking loss was maximal at 30 days and minimal at 60 days. Sensory evaluation revealed that T4 enhanced the tenderness of the dish (4.17), but T2 diminished its juiciness, taste, and overall acceptability (2.50). Kiwifruit extracts generally rendered food softer, enhanced its mineral content, and increased its palatability. Pineapple extracts, however, enhanced moisture but diminished the food's palatability and protein content at elevated quantities.